1989
DOI: 10.1111/j.1365-2141.1989.tb04268.x
|View full text |Cite
|
Sign up to set email alerts
|

Rabbit serum alpha‐2‐macroglobulin binds to liver ferritin: association causes a heterogeneity of ferritin molecules

Abstract: Rabbit liver ferritin is unusual since it forms two discrete electrophoretic bands at the beta position of molecular dimers (Santambrogio & Massover, 1987). The present studies have sought to identify the nature of a 170 kDa non-ferritin polypeptide that is uniquely present in the larger beta band. Ultrastructural, immunological and biochemical results all indicate that this polypeptide is a subunit of the plasma protein. alpha-2-macroglobulin. Experimental results show that rabbit serum alpha-2-macroglobulin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 53 publications
0
32
0
Order By: Relevance
“…It is proposed that an autoantibody to ferritin might be a general ferritin binder along with alpha-2-macroglobuli n [15,22]. In hors es, alpha-2-macroglobulin and fibrinogen have been identified as FBPs [15,19], and these proteins are involved in blood coagulation and plasma fibrinolytic enzyme systems [6,19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is proposed that an autoantibody to ferritin might be a general ferritin binder along with alpha-2-macroglobuli n [15,22]. In hors es, alpha-2-macroglobulin and fibrinogen have been identified as FBPs [15,19], and these proteins are involved in blood coagulation and plasma fibrinolytic enzyme systems [6,19].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, horse fibrinogen has been found to be a plasma-specific FBP that inhibits immunoassay of ferritin and binds to horse ferritin [19]. In mammals, although alpha-2-macroglobulin is known to be a common FBP [15,22], anti-ferritin autoantibodies have recently been identified as FBP [17,29]. The purpose of our study was to purify and identify FBPs from horse serum.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that in addition to ferritin, human serum contains ferritinbinding protein(s) (4 -6). In one study, partial purification revealed ferritin binding activity to be present in the ␤-2 region of human serum (6); a study of rabbit serum suggested that ␣ 2 -macroglobulin has ferritin binding activity (7). The role of ferritin-binding proteins(s) is uncertain; however, it has been suggested that ferritin-binding proteins may serve as acquired receptors for ferritin itself.…”
mentioning
confidence: 99%
“…Such a rapid clearance may be due to interaction with ferritin receptors on hepatocytes (100) which appear to have a higher affinity for liver ferritin than for serum ferritin, at least in experiments on rats. Rapid clearance may also be initiated by interaction with ferritin binding proteins in the plasma (101)(102)(103)(104). Several isoferritins may be released into the plasma but the ones which normally accumulate are L 24 molecules and glycosylated molecules that are rich in L-subunits and again contain little iron.…”
Section: Origin Of Serum Ferritin and Its Clearance From The Circulationmentioning
confidence: 99%